Investigating the effectiveness of ailurophobia treatment using virtual reality technique compared to metacognitive therapy: a randomized clinical trial - Alireza Ebrahimi; Farzad Akbarzadeh; Negar Asgharipour; Razie Salehabadi; Malihe Arjamandi (BMC Psychology)
Abstract Background Fear of cats as a specific phobia disorder can cause disruption in some aspects of the affected people’s lives. On the other hand, due to the fact that the two approaches of metacognitive treatment and behavioral therapy methods such as virtual reality are considered common treatment methods in anxiety disorders; It seems that it is necessary to examine the two approaches based on the effectiveness, durability and cost-benefit issue to present and introduce to therapists. Methods The present study was a Randomized Clinical Trial study that was conducted on 28 patients with Ailurophobia. Based on simple random sampling, the participants were allocated in two groups: metacognitive intervention and virtual reality intervention. In order to collect data, demographic information questionnaire, cat anxiety questionnaire and researcher-made cat fear questionnaire were used. Data analysis was done with SPSS version 22 software and statistical tests of chi-square, t, analysis of variance. An alpha level of less than 0.05 was considered as a significant level. Results The results of the study showed that there was a statistically significant difference between the average anxiety score in the two groups of virtual reality and metacognitive therapy (P˂0.001). So that in the virtual reality group, the anxiety score was significantly reduced. Also, other results of the study indicated that the mean score of the fear of cats scale was significantly lower in the virtual reality group than in the metacognitive therapy group (P˂0.001). Conclusions Although both treatment approaches based on virtual reality and metacognition are effective in reducing the level of anxiety and fear of cats in patients with Ailurophobia; However, the effectiveness and continuity of treatment in people receiving virtual reality treatment are more significant. IRCT registration number IRCT20230105057057N1. Registration date: 2023-03-04. Registry Iranian Registry of Clinical Trials.